Pengembangan Lembar Kerja Peserta Didik (LKPD) Berorientasi Pendekatan Kontekstual Pada Materi Penyesuaian Diri Makhluk Hidup Terhadap Lingkungannya Untuk Kelas VI - Candra Melati Putra; Irwan Koto; Endang Widi Winarni (UNIB Press, 2022)
This study aims to develop LKPD oriented contextual approach to the material adaptation of living things to their environment class VI and to describe the feasibility and responses of users (teachers and students). The research was conducted at SDN Muara Kuis Muratara in class VI. This research is a research and development research with the Four D (4D) model. The object of this research is LKPD with contextual approach orientation. The research stages are define, design, develop and disseminate. The instrument used is a feasibility test questionnaire and teacher interviews and student questionnaires. The feasibility test was carried out by 6 validators, namely 2 material experts, 2 language experts and 2 display experts. The user response test was carried out on 15 grade VI students and 1 teacher at SDN Muara Kuis Muratara. Data analysis used percentage technique and processed descriptively. The contextual elements in the LKPD are relating (connecting), experiencing (experience), applying (application), cooperating (working together), and transfering (moving). The results of the LKPD feasibility test are contextually oriented by the validator in terms of material aspects, language aspects and presentation aspects. Feasibility of the material obtained 0.81 (very feasible), language 0.66 (feasible criteria), display 0.80 (very feasible). The results of the test using the LKPD oriented contextual approach, a response was obtained that the LKPD had met the needs of teachers to be used as teaching materials to support science learning in class VI and received positive criteria by students on aspects of LKPD material quality, LKPD display aspects, aspects of material presentation, and aspects of LKPD. benefits through the distribution of questionnaires. It can be concluded that the use of contextual approach-oriented LKPD is feasible and positive to be used as teaching material in grade VI SD.